Social media usage and its impact on Malaysian organizations / Farzana Parveen Tajudeen - Tajudeen, Farzana Parveen (2014)
The usage of social media among organizations is growing tremendously. Since investments in these technologies are increasing, it is important to investigate the impact of social media usage on organization. This study, using a mixed method approach investigates the factors that influence the social media usage, the various purposes of using social media, and its subsequent impact on organizational performances. The first phase of the research using web content analysis revealed that Facebook is the most popular social media presence among Malaysian organizations. It was also found that there are a higher percentage of organizations that use Facebook for interactivity with stakeholders. The second phase of the study using in-depth interviews guided the development of the research model for the study. The results of the qualitative analysis showed that social media is used for various purposes in organizations and has a greater positive impact on the organizational performances in terms of customer service, information accessibility, and cost reduction for marketing and customer service activities. Finally, the third phase of the study used the survey method to test and validate the model that was derived from the interviews and literature review. The integrated model with TOE framework as a base was used. The results of the analysis showed that factors such as interactivity, relative advantage, compatibility, and institutional pressure had a positive effect on using social media. Similarly, the usage of social media had a stronger, positive impact on organizational performance. This study, by integrating various theories, develops an integrative model and contributes to the scholarly research, literature of the information systems, and strategic management field. The study also helps organizations to understand the benefits of social media usage and provide justification for social media investments in organizations.